ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI: Studi Pada Kampus IV Kediri Poltekkes Malang - Faiz Fadl Lulloh, Ahmad; Sugiarto, Dodik (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2023)
This study aims to determine the factors that influence employee performance. The research was conducted at Campus IV Poltekkes Malang in Kediri. The type of research used is research design research. This research design uses a quantitative approach that is associative. This research is a causal associative research using a quantitative approach. The population was taken from the employees of Campus IV Kediri Poltekkes Malang, totaling 42 people. The method of determining the number of samples was carried out using saturated sampling. The number of samples taken from Campus IV Kediri Poltekkes Malang were all employees, totaling 42 people. The data collection technique used a questionnaire. The data analysis technique uses multiple linear regression t-test and F-test. Based on the results of multiple linear regression analysis, it can be concluded that simultaneously has a significant effect on employee performance. Partially it can be concluded that each independent variable consisting of discipline and ability has a significant influence on the dependent variable of employee performance.